A192 DEPLETING ASCL2 IN ESOPHAGEAL ORGANOIDS TO INVESTIGATE ITS ROLE IN STEM CELLS MAINTENANCE. (26th February 2020) - Hamilton, M; Jean, D; Giroux, V
Abstract: Background: Recently, the first population of stem cells in the esophageal epithelium was identified with the help of the Keratin 15 ( Krt15 ) marker. However, little is known about the mechanisms underlying the expansion and the function of stem cells in the esophagus. It was shown that ASCL2, a transcription factor, is upregulated in Krt15+ cells compared with Krt15 - cells. ASCL2 is a gene target of the Wnt/β-catenin pathway, which act as a regulator of proliferation and maintenance of the stemness state. The ultimate goal of my research project is to determine the role of ASCL2 in the maintenance of esophageal stem cells and to identify his binding partners. Aims: To investigate the role of ASCL2 in esophageal epithelial biology, we aim at establishing Ascl2 knockout esophageal organoid lines. Methods: Lentiviral infection and CRISPR/Cas9 knockout approach were optimized in mouse esophageal organoids. ASCL2was invalidated with CRISPR/Cas9 and/or inducible specific shRNAs in primary mouse esophageal cell line and organoids. Antibodies directed against ASCL2 were also tested to validate cell lines. Results: First, to optimize lentiviral infection in mouse esophageal organoids, we produced GFP-expressing lentiviruses. Viruses were then concentrated and incubated with a single cell suspension of mouse organoid cells under gentle activation. Infected cells were embedded in Matrigel and grown in organoids. GFP+ cells were then selected using an antibiotic resistance strategy. Second, we used our optimized lentiviral infection protocol to express specific gRNAs in mouse esophageal organoids, which were previously screened in a primary mouse esophageal cell line. Knockout were validated using Western Blot. Invalidation of ASCL2 was performed using CRISPR/Cas9 and inducible shRNAs. We also validated three commercially available ASCL2 antibodies in WB and IF. Conclusions: ASCL2 is expressed in the mouse esophagus tissue and organoids, and it can be invalidated in cell lines and organoids. Funding Agencies: NSERC, CRC Tier2